2011
DOI: 10.1097/qai.0b013e31822d0433
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelated Transmission of HIV-1 and Cytomegalovirus During Gestation and Delivery in the Offspring of HIV-Infected Mothers

Abstract: Our objective was to analyze, in formula-fed infants, correlates of HIV mother-to-child transmission, including cytomegalovirus (CMV) infection. HIV-infected infants were matched with HIV-uninfected by maternal HIV RNA in a case-control design. Infant CMV infection was determined by CMV-IgG at 18 months and timed by earlier CMV-IgM or -DNA. Correlations were assessed using logistic regression. In utero HIV infection was independently associated with congenital CMV infection (P=0.01), intrapartum HIV infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
4
24
3
Order By: Relevance
“…There was a significantly higher prevalence of congenital CMV infection among HIV-infected neonates, compared with HIV-uninfected neonates (Table 1). Similar results were seen in a smaller study of 51 HIV-exposed infants in Kenya [29], as well as in a retrospective case-control analysis of HIV-exposed infants enrolled in a clinical trial comparing long and short durations of maternal and infant use of zidovudine for the prevention of MTCT of HIV in Thailand [28]. Most recently, a subanalysis of data from a study in Malawi revealed that congenital CMV infection was more common among infants with in utero HIV infection, compared with HIV-exposed-uninfected infants (Table 1) [30].…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…There was a significantly higher prevalence of congenital CMV infection among HIV-infected neonates, compared with HIV-uninfected neonates (Table 1). Similar results were seen in a smaller study of 51 HIV-exposed infants in Kenya [29], as well as in a retrospective case-control analysis of HIV-exposed infants enrolled in a clinical trial comparing long and short durations of maternal and infant use of zidovudine for the prevention of MTCT of HIV in Thailand [28]. Most recently, a subanalysis of data from a study in Malawi revealed that congenital CMV infection was more common among infants with in utero HIV infection, compared with HIV-exposed-uninfected infants (Table 1) [30].…”
Section: Resultssupporting
confidence: 82%
“…Ten of these addressed congenital CMV infection [12, 18, 2124, 26, 2830]. One early study in the United States examined data from 154 infants born during 1988–1995 [21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kovacs et al [16] had previously suggested that the increase in the coinfection rate could be caused by higher levels of cervical CMV shedding in HIV-infected women who also transmitted HIV to their infants at birth, as positive cervical CMV cultures had also been shown to correlate with perinatal CMV infection [32]. Also, because of impaired immunological surveillance, HIVinfected infants are unable to abort incipient CMV infections and are thus more susceptible to horizontal postnatal CMV acquisition [16,33]. However, maternal advanced HIV disease (i.e., CD4 counts ≤ 200 cells/mm 3 , viral load > 100,000 copies/mL), which could also explain a higher mother-to-child transmission of HIV and a higher shedding of more CMV in the saliva, cervix tissue, or urine, was not found to be significantly associated with CMV infection in the young infants in this study.…”
Section: Discussionmentioning
confidence: 99%